O23: CHARACTERISING PATIENT‐DERIVED COLORECTAL CANCER TISSUE‐ORIGINATED ORGANOIDAL SPHEROIDS FOR HIGH‐THROUGHPUT MICROFLUIDIC APPLICATIONS. (27th April 2021) - Khot, MI; Levenstein, M; Coppo, R; Kondo, J; Inoue, M; Kapur, N; Jayne, DG
Abstract: Introduction: Three‐dimensional (3D) cell models have gained reputation as better representations of in vivo cancers as compared to monolayered cultures. Recently, patient tumour tissue‐derived organoids have advanced the scope of complex in vitro models, by allowing patient‐specific tumour cultures to be generated for developing new medicines and patient‐tailored treatments. Integrating 3D cell and organoid culturing into microfluidics, can streamline traditional protocols and allow complex and precise high‐throughput experiments to be performed with ease. Method: Patient‐derived colorectal cancer tissue‐originated organoidal spheroids (CTOS) cultures were acquired from Kyoto University, Japan. CTOS were cultured in Matrigel and stem‐cell media. CTOS were treated with 5‐fluorouracil and cytotoxicity evaluated via fluorescent imaging and ATP assay. CTOS were embedded, sectioned and subjected to H&E staining and immunofluorescence for ABCG2 and Ki67 proteins. HT29 colorectal cancer spheroids were produced on microfluidic devices using cell suspensions and subjected to 5‐fluorouracil treatment via fluid flow. Cytotoxicity was evaluated through fluorescent imaging and LDH assay. Result: 5‐fluorouracil dose‐dependent reduction in cell viability was observed in CTOS cultures ( p <0.01). Colorectal CTOS cultures retained the histology, tissue architecture and protein expression of the colonic epithelial structure. Uniform 3D HT29 spheroids were generated in the microfluidic devices. 5‐fluorouracil treatment of spheroids and cytotoxic analysis was achieved conveniently through fluid flow. Conclusion: Patient‐derived CTOS are better complex models of in vivo cancers than 3D cell models and can improve the clinical translation of novel treatments. Microfluidics can streamline high‐throughput screening and reduce the practical difficulties of conventional organoid and 3D cell culturing. Take‐home message: Organoids are the most advanced in vitro models of clinical cancers. Microfluidics can streamline and improve traditional laboratory experiments.